Effect of Controlled Deposition of ZnS Shell on the Photostability of CdTe Quantum Dots as Studied by Conventional Fluorescence and FCS Techniques1. Issue 18 (3rd November 2015) - Patra, Satyajit; Seth, Sudipta; Samanta, Anunay
Abstract: The effect of one and two monolayers of ZnS shells on the photostability of CdTe quantum dots (QDs) in aqueous and nonaqueous media has been studied by monitoring the fluorescence behavior of the QDs under ensemble and single‐molecule conditions. ZnS capping of the CdTe QDs leads to significant enhancement of the fluorescence brightness of these QDs. Considerable enhancement of the photostability of the shell‐protected QDs, including the suppression of photoactivation, is also observed. Fluorescence correlation spectroscopy measurements reveal an increase in the number of particles undergoing reversible fluorescent on–off transitions in the volume under observation with increasing excitation power; this effect is found to be more pronounced in the case of core‐only QDs than for core–shell QDs. Abstract : In a ZnS shell : The effect of ZnS shell deposition on the photoluminescence efficiency and photostability of a CdTe core is demonstrated by using conventional fluorescence and fluorescence correlation spectroscopy techniques. CdTe/ZnS not only exhibits high photoluminescence, but also shows exceptional photostability.